VOICES EMPOWERED: IRANIAN WOMEN AND WEBLOGS - Zargarian, Tannaz (AoIR Selected Papers of Internet Research, 2018)
Access to the Internet in 1998 created a unique sphere encompassing both public and private characteristics while offering a new form of communication, identity, and political participation (Rheingold 2000). As a result, access to the Internet provided women with an alternative way of defying the traditional masculine culture through "connection and communication" and "identity transformation" (Nouraei-Simon 2005). The Internet ameliorated Iranian women’s ability to contribute to the accelerating development of an online culture that offers a significant change to the definition of empowerment as it shifts the boundaries of the public and private realms, allowing Iranian women to seek self-determination despite Islamic ideology (Jones, 1997). This work shows how the weblog has become one of the key tools to challenge social barriers in the quest for Iranian women’s rights (Sreberny & Khiabany, 2010). This paper will critically examine the use of weblogs by some Iranian women to break the gender oriented restrictive rules imposed upon them by the patriarchal elements in higher education by exploring how and in what ways women advocate for their own and others’ rights and equality? This paper incorporates a critical textual analysis of primary and secondary academic sources. It integrates a critical feminist approach and have collected data from the work of female scholars, activists, bloggers, and filmmakers and have brought forth the unheard experiences of some Iranian women in higher education.